Factors that influence investment decision making among potential individual investors in Malaysia / Atikah Zulaikha Ahmad Zaidi and Nor Suziwana Tahir - Ahmad Zaidi, Atikah Zulaikha; Tahir, Nor Suziwana (Universiti Teknologi MARA, Shah Alam, 2019)
Individual investments behaviour is concerned with choices about purchases of small amounts of securities for his or her own account. Decision tools often support investment decisions. It is assumed that information structure and the factors in the market systematically influence individuals’ investment decisions as well as market outcomes. Decision tools often support investment decisions. It is assumed that information structure and the factors in the market systematically influence individuals’ investment decisions as well as market outcomes. Investor market behaviour derives from psychological principles of decision making to explain why people buy or sell stocks. These factors will focus upon how investors interpret and act on information to make investment decisions. The purpose of the study was to identify the factors that influence investment decision making among potential individual investors in Malaysia. Three behavioural factors might influence investment decision making which are accounting-information, firm-image coincidence and personal-financial-needs. A set of questionnaire was distributed to 384 potential investors in Malaysia specifically in housing area of Klang Valley as population of this study. Based on the findings, it showed that there is positive relationship between accounting-information, firm-image-coincidence and personal-financial-needs in investment decision making. Hence, between these three behavioural factors, accounting-information, firm-image coincidence and personalfinancial-needs, the main influential factor is accounting-information. This study also proposed a future research for investment decision making and give implications to the potential investors, community, organization, policy makers and investment practitioners.